Integrating lean principles in fire safety engineering for private Al-Quran memorization (Tahfiz) school buildings: A conceptual framework - Siti Rosnah, Salman; Rahmawati, S.; Sisca Mayang Phuspa, .; Nurud Suria, Suhaimi; Azizan, Ramli (Penerbit UMP, 2025)
The adoption of lean principles and the establishment of a lean culture are continuing trends in both construction and post-construction buildings. This paper will examine how lean principles and fire safety management practices are integrated into the design, supply, construction, occupation, refurbishment, and demolition phases of the Private Al-Quran Memorization (Tahfiz) School (PTS). A deadly fire at Pusat Tahfiz Darul Quran Ittifaqiyah, a religious school in Kampung Datuk Keramat, in 2017, and other fire incidents that caused heightened attention on safety in these institutions led to the start of this study. This poses a significant challenge that requires immediate attention to the infrastructure and fire prevention systems of PTS. It is important to effectively implement fire safety measures to protect people, school buildings, and property from the catastrophic effects of fire. To address this issue, Lean Principles are being adopted in fire safety management, with a focus on the performance of the PTS infrastructure as a prevention approach. Lean Principles are commonly used in Lean Manufacturing, Lean Design, Lean Construction, and Lean Maintenance, and have been widely accepted by professionals worldwide. Prevention through Design (PtD) can be initiated as a general prevention principle, with various Lean Tools implemented throughout the PTS building lifecycle, including designing, construction, occupying, demolishing, and modification processes. Despite the integration of Lean Principles into fire safety engineering is yet to be studied and introduced effectively, the framework has potential benefit in developing legislation, rules, guidelines, and good practise in the government/regulatory body that could enhance the fire prevention system in the PTS.